Analysis Personalitytest of Employee Personality on Job Satisfaction While Working at PT KAI DAOP Indonesia - Samsunu Dwi Putro; Susanto Tirtoprojo (International Journal of Science and Applied Science: Conference Series, 2021)
This study aims to determine the analysis of thetest of personality employees' personality on job satisfaction while working at PT KAI DAOP IV Indonesia. The research method used is descriptive qualitative. The research population used in this study were all employees of PT KAI (Persero) in DAOP VI Yogyakarta, Indonesia. The sample of this research is the employees of PT KAI (Persero) in the Operations Division, totaling 227 employees. The sampling technique of this research is using amodel purpose sampling. The research procedure was carried out by observation, interviews, questionnaires/questionnaires. Theresearch instrument personality testamounted to 38 items. The measurement of personality in the field of psychology uses a linkert scale which is expressed in the form of numbers 1-4 or a scale of 1-5. The results showed that the results of the data on the number of respondents based on gender were judged by the majority of male respondents by 97%, while female respondents by 3%. The results of the data on the number of respondents based on age <25 years are 2%, ages 25-35 are 70%, 36-45 are 21% and 46-55 are 7%. diagram of the results of data on the number of respondents based on years of service of employees ranging from < 5 years by 8%, 5 - 10 years by 42%, 10-15 years by 35%, 15 - 20 years by 5%, 20 - 25 years by 10%, >25 years at 0%. The results of the analysis of the personality test of employee personality on job satisfaction while working at PT KAI DAOP IV Yogyakarta, Indonesia as a whole obtained a percentage that was still low below 50%. The conclusion of this study is that the personality test of the employee's personality on job satisfaction while working in the PT KAI DAOP IV Yogyakarta environment as a whole obtains a low percentage so that it is necessary to increase and empower the personality of employees.